BURNOUT SYNDROME IN NURSING PROFESSIONALS IN PUNTA ARENAS, CHILE - Gutiérrez, Karina Pamela Martinic; Ramos, Flávia Regina Souza; Dalmolin, Graziele de Lima (My University, 2020)
ABSTRACT Objective: to identify the prevalence of burnout syndrome in nursing professionals in Punta Arenas, Chile. Method: quantitative, descriptive, cross-sectional research in a sample of nursing professionals from Punta Arenas, Chile. Data were collected between January and March 2019, using the Maslach Burnout Inventory and a sociodemographic questionnaire. Descriptive statistics were applied in the data analysis. Results: 163 individuals participated in the study. 18% of the sample suffered from burnout syndrome, who were female young adults, i.e. between 20 and 40 years of age, and who worked in direct user care. Conclusion: the prevalence of burnout in the as-yet-unexplored place of study and in different work scenarios, such as education, management, and hospital-based and primary health care, confirms the implications of this study for occupational health in this population. This knowledge offers recent evidence to ground the implementation of occupational health promotion policies and strategies in Chilean nursing professionals.
Keywords: burnout, professional; nursing; occupational health; nursing staff; stress, psychological